2018
DOI: 10.1525/mp.2018.35.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Average Pitch Height and Perceived Emotional Expression Within an Unconventional Tuning System

Abstract: Prior research has amply documented that happy music tends to be faster, louder, higher in average pitch, more variable in pitch, and more staccato in articulation, whereas sad music tends to be slower, lower, less variable, and more legato in articulation. However, the bulk of existing studies are either correlational or allow these expressive cues to covary freely, thereby making it difficult to confirm the causal influence of a given cue. To help address this gap, we experimentally assessed whether the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Another notable finding of this study is the strong effect of average pitch height in both models, supporting the theory that high pitch is associated with positive affect, with positive applying to both pleasantness and happiness [28,5152,31]. These correlations may partly be explained by the relationship between music and vocal affect expression [35,7273].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Another notable finding of this study is the strong effect of average pitch height in both models, supporting the theory that high pitch is associated with positive affect, with positive applying to both pleasantness and happiness [28,5152,31]. These correlations may partly be explained by the relationship between music and vocal affect expression [35,7273].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have found inverse relationships or an inverted-U- shaped function between preference and pitch height (see [53] for an overview of those studies), but it is important to note that the range of frequencies used is often larger in the studies reporting an inverse relationship or an inverted-U-shape. In the previously discussed study by Friedman et al [28], the positive relation between average pitch and happiness ratings was found despite the unconventional nature of the scale and was independent of interval sizes, which is suggestive of it being a robust effect.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations